Large gap between attitude and action in tuberculosis preventive treatment among tuberculosis-related healthcare workers in eastern China - Wang, Fei; Ren, Yanli; Liu, Kui; Peng, Ying; Chen, Xinyi; Chen, Bin; Jiang, Jianmin (Frontiers in Cellular and Infection Microbiology, 2022)
Abstract Objectives Health care workers (HCWs) are at high risk for latent tuberculosis infection (LTBI) because of occupational exposure, and the attitudes and behaviors of frontline tuberculosis HCWs toward preventive treatment of LTBI in eastern China remain unknown. The aim of this study was to explore the attitudes and actual behaviors of TB-related HCWs toward tuberculosis preventive treatment (TPT) and to analyze the relevant factors influencing the attitudes of HCWs. Methods A stratified random sample of 28 TB-designated hospitals was selected in Zhejiang Province, China. All TB-related HCWs in the selected hospitals were recruited to answer questionnaires and were tested for LTBI by the TB interferon gamma release assay. The action of TPT was followed up two years after the survey. Univariate analysis and binary logistic regression models were used to analyze the factors influencing the prophylactic treatment intention of HCWs. Results A total of 318 TB-related HCWs were recruited in 28 TB-designated hospitals; 62.3% of them showed positive attitudes toward preventive treatment, while the rest were reluctant to treat positive LTBI prophylactically. Multifactorial regression analysis revealed that the factors influencing the attitudes of HCWs were mainly education level, household income, history of alcohol consumption, and workplace. And when the reasons for not wanting preventive treatment were analyzed, it was found that the most people refused treatment because of drug side effects, followed by the belief that treatment was ineffective, wanting to wait until the onset of the disease, and that it was too much trouble to take the medication. According to the result of follow-up survey, only one of these 62.3% of HCWs underwent prophylactic treatment. Conclusion This study reveals different attitudes toward TB preventive treatment among TB-associated HCWs in eastern China and a large gap between attitudes and actual action. Management of HCWs with latent infection still needs further strengthening.